Vitamin D quality control 7.000 IU: Comparative study between masterfull and industrialized formulations (Research, Society and Development, 2022)
With the beginning of the COVID-19 pandemic, the search for strengthening the immune system had an exorbitant growth, for this, people started to use medicines and supplements that provide such benefit, such as Vitamin D. In this context, the present The objective of this study was to evaluate, through quality control, whether Vitamin D 7000 IU from dispensing and handling pharmacies are within the standards stipulated by the United States Pharmacopeia and if they present the amount in IU they guarantee to have. Therefore, supplements from 3 compounding pharmacies and 3 industrialized vitamins D were tested, using the tests contained in the United States Pharmacopeia, namely, the average weight, disintegration test, purity test, and dosage. The results obtained were that, in the tests of average weight and disintegration, the manipulated and industrialized samples were approved, in the purity and dosage tests they were not approved, as the values ​​resulting from these analyzes were discrepant with those established in the United States Pharmacopeia. With this, it was concluded that the compounding pharmacies and the pharmaceutical industries have flaws in their respective quality controls, which demands a special look, since such flaws lead to products without a guarantee of safety and effectiveness.